Religious Dialogue on Social Media: The Khilafah Issue Between Pluralist and Scripturalist Muslims - Muhammad Kasim (STAI AL-FALAH CICALENGKA, 2022)
Great efforts have been exhausted to bring religion closer to the media (as opposed to bringing media closer to religion), or to break down the traditional boundaries between